Etude de l'impact des icebergs Antarctiques sur l'Océan Austral - Bouhier, Nicolas (Université de Bretagne occidentale, 2017)
The Antarctic polar ice cap constrains a freshwater flaux into the Austral Ocean through two equally important pathways : a localized and immediate injection through the melting of ice-shelves bases, and a delayed offshore injection through the calving and subsequent melt of icebergs. Some studies reckon that melting icebergs have the capacity to alter the hydrological and biogeo-chemical characteristics of the water column. The numerical models trying to evaluate this impact have shown contrasting results. Yet, they might suffer from a poor representation of the icebergs, namely due to our limited knowledge on both the spatial and size distributions of the icebergs, or even the processes involved in their mass loss. A new method using satellite altimetry measurements has lead to the creation of a database mapping Antarctic icebergs distribution with an unprecedented spatial and temporal coverage. Our joint analysis between these data and sea ice concentration fields highlights a possible transport of the freshwater injected by an iceberg and its impacts on sea ice.We also analyze the links between icebergs of different sizes : the large ones can be seen as ice buffers that diffuse across the whole ocean when breaking into small fragments of various sizes. We finally study the evolution of two giant icebergs, suggest the first parametrization of the fragmentation process and analyze the subsequent size distribution of the fragments. These results can be valuable to account in a more realistic way the fresh water flux constrained by icebergs in models. La calotte polaire Antarctique conditionne un flux d’eau douce dans l’océan Austral par deux voies d’égale importance : une injection immédiate et localisée par fonte des plateformes glaciaires, et une injection « offshore » et différée par production (« vêlage ») puis fonte d’icebergs. On estime ainsi que les icebergs, en fondant, pourraient modifier les caractéristiques hydrologiques et biogéochimiques de la colonne d’eau. Les modèles numériques visant à ...